Serum creatinine and estimated glomerular filtration rate (eGFR) in early pregnancy and changes during the pregnancy. - Suneth Buddhika Agampodi; Thilini Chanchala Agampodi; Gayani Shashikala Amarasinghe; Janith Niwanthaka Warnasekara; Ayesh Umeshana Hettiarachchi; Imasha Upulini Jayasinghe; Iresha Sandamali Koralegedara; Parami Abeyrathna; Shalka Srimantha; Farika Nirmani de Silva; Sajaan Praveena Gunarathne; Nuwan Darshana Wickramasinghe (Public Library of Science (PLoS), 2023)
Renal functions in pregnancy undergo rapid changes, and the thresholds for normal values are a major research gap and are still debatable. The lack of prospective population-based studies with early pregnancy recruitment hampered the decision-making process on the best thresholds to be used in clinical practice. We present the serum creatinine (sCr) and sCr-based estimated glomerular filtration rates (eGFR) in early pregnancy with changes over the gestational period in a large prospective, community-based cohort, the Rajarata Pregnancy Cohort (RaPCo). We carried out a community-based prospective cohort study with 2,259 healthy pregnant women with a gestation period of less than 13 weeks and without pre-existing medical conditions. Gestational period-specific sCr and sCr-based eGFR were calculated for different age strata, and the participants were followed up until the second trimester. Renal functions of pregnant women were compared with 2.012 nonpregnant women from the same geographical area. The mean (SD) sCr of the 2,012 nonpregnant women was 62.8(12.4) μmol/L, with the 97.5th percentile of 89.0 μmol/L. Among the pregnant women, mean (SD) sCr was 55.1(8.3), 52.7(8.1), 51.1(9.1), 47.1(7.2), and 49.3 (9.9), while the 97.5th percentile for sCr was 72.4, 69.1, 70.0, 63.6, and 66.0 μmol/L respectively during the 4-7, 8-9, 10-12, 24-27 and 28-30 weeks of gestation. The average sCr value was 84.7% and 76.4% of the nonpregnant group, respectively, in the first and second trimesters. The mean eGFR was 123.4 (10.7) mL/min/1.73 m2 in the first trimester and increased up to 129.5 mL/min/1.73 m2 in the 24th week of gestation. The analysis of cohort data confirmed a significant reduction in sCr with advancing pregnancy (p<0 .001). This study provides thresholds for renal functions in pregnancy to be used in clinical practice. Clinical validation of the proposed thresholds needs to be evaluated with pregnancy and newborn outcomes.